Selected Aspects of The Sustainability Teaching Model Environmental, Social and Governance (ESG) Issues at Universities - Katarzyna CHŁAPEK; Sylwia KRAJEWSKA; Izabella EMERLING (Communications of International Proceedings, 2023)
The changing economic reality, unexpected crisis situations and the need to implement the ESG (environmental, social and governance) idea imply the search for methods and forms of teaching. The specific role of universities in this area has been identified. During the conducted literature research, an existing gap was noticed, both in literature and in terms of tools. The aim of the article is to present methods and forms of teaching important in the aspect of communicating sustainability issues, environmental, social and governance (ESG) at the university.  The basic research methods to achieve this goal are own research, in which a questionnaire and critical literature studies were used, and in formulating conclusions – statistical methods as well as deduction and synthesis. During the conducted research, answers were sought to the following research questions: what form of classes would be most effective for disseminating knowledge about ESG and what didactic methods should be used to disseminate knowledge about ESG? The results obtained as part of the research indicate that both in terms of methods and forms of teaching, a balanced approach and the choice of a hybrid solution are very important. The article presents a proposal for solutions that can be used in many universities.
Keywords: ESG; sustainability; education in the field of sustainable development; teaching model